Challenges of Government Funding Model on Public Universities - Letsebe, Lametse Nono; Ebewo, Patrick Ebong; Nesamvuni, Alufheli Edgar (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The purpose of this study was to examine the challenges posed by the funding model on the transformation of public universities into entrepreneurial universities in Botswana to determine how the model affects or influence the adoption of an entrepreneurship model in public universities. Design/methodology/approach: A qualitative study with 30 participants from four (4) public universities was conducted with the use of a semi structured interview. The sample was drawn from top management in each of the universities. Data was transcribed, coded and grouped into themes with the use of Atlas ti software version 22. Findings: Government funding model hinders the transition of public universities into entrepreneurial universities. Firstly, the funding model is bureaucratic in nature. Secondly, the model forces public universities to operate from a zero budget. Thirdly, the model encourages irresponsible spending. The less funds a university utilizes the higher the cut in funding in the next budget allocation cycle. Fourthly, the funding model has a short budget cycle which hinder public universities to conduct long term projects which brings more financial returns compared to short term projects. Lastly, while research is seen as a key driver to aid the transformation, the model does not cater for a research and transformation budget. Research limitations/Implications: The study was limited to the enquiry of the challenges of the government funding model on the transition of Botswana public universities into entrepreneurial universities. The study focused on insights from senior management of public universities. While this formed a good basis for this exploratory study, future studies may consider a quantitative study with other key players to validate these findings. Further research is therefore recommended amongst middle management and university students in public universities. Practical Implications: This research improves knowledge in the systematic executions for developing strategies that are likely to influence and support the entrepreneurship model in Botswana's public universities. Originality/Value: This research was the first attempt to examine the challenges posed by the funding model on the transition of public universities into entrepreneurial universities in Botswana. Recommendations were made for government policy makers to review the current funding model with the view to develop a new model to support an entrepreneurship model in public universities. Paper type: Research Paper